The Effect of Social Media Marketing Activities Through Brand Awareness and Brand Image on Brand Loyalty and Emotional Attachment in Traveloka - Nadino Rinaldi, Muhammad Adrian Daffa; Heppy Millanyani; Nurvita Trianasari (Publisher Cv. Inara, 2024)
Growth technology Which fast especially development Internet in Indonesia Which give Lots Of convenience for do interaction. See development Internet Which so fast proven with increasing Internet and social media use in Indonesia. The purpose of this research is to determine the influence of social media marketing activities on brand loyalty and emotional attachment and brand equity which includes brand awareness and brand equity mediates the relationship between the two variables. Traveloka is the object of this research is company Which move on field industry tourist. Method study Which used in study This is method quantitative by collecting data through questionnaires that use scales likert. The number of samples taken in this research was 250 respondents. Criteria Which used for respondents covers followers from Instagram Traveloka And Already do transaction minimum 2x. Analysis data use Structural Equation Modeling (SEM) and processed using Smart software PLS-SEM. Keywords: Social Media Marketing Activities, Brand Equity, SEM PLS, E-Tourism